2017
DOI: 10.1007/s00280-017-3383-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous pan-class I phosphatidylinositol 3-kinase (PI3K) inhibitor [14C]copanlisib (BAY 80-6946) in a mass balance study in healthy male volunteers

Abstract: PurposeTo determine the pharmacokinetics of radiolabeled copanlisib (BAY 80-6946) in healthy male volunteers and to investigate the disposition and biotransformation of copanlisib.MethodsA single dose of 12 mg copanlisib containing 2.76 MBq [14C]copanlisib was administered as a 1-h intravenous infusion to 6 volunteers with subsequent sampling up to 34 days. Blood, plasma, urine and feces were collected to monitor total radioactivity, parent compound and metabolites.ResultsCopanlisib treatment was well tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…This data suggests that copanlisib has selective uptake/binding by/to red blood cells. Gerisch et al (2017) also reported the selective uptake of copanlisib by human red blood cells. Because of this, the blood concentrations were higher than in plasma in humans.…”
Section: Resultsmentioning
confidence: 96%
“…This data suggests that copanlisib has selective uptake/binding by/to red blood cells. Gerisch et al (2017) also reported the selective uptake of copanlisib by human red blood cells. Because of this, the blood concentrations were higher than in plasma in humans.…”
Section: Resultsmentioning
confidence: 96%
“…Elimination of copanlisib and its metabolites is predominantly through hepatic metabolism and biliary excretion with more than 90% of in vitro metabolism mediated by cytochrome P450 (CYP) 3A4 and less than 1% by CYP1A1. 24 Aforementioned exposure and other PK parameters remained similar following multiple administrations (every second day × 5), signifying lack of compound accumulation of compound or metabolic process alterations. An alternative dosing schedule of intravenous copanlisib twice a day once weekly for also showed equivalent antitumor activity.…”
Section: Pharmacokineticsmentioning
confidence: 89%
“…Given the predominant hepatic elimination of copanlisib, 24 concomitant use of copanlisib with a strong CYP3A inducer should be avoided and the package insert recommends a dose decrement to 45 mg in this setting. Manufacturers also recommend a dose decrease to 45 mg in case with moderate hepatic impairment (Child Pugh Class B).…”
Section: Administrationmentioning
confidence: 99%
“…In a smaller Phase I study by Gerisch et al, six healthy volunteers were observed with similar pharmacokinetics to the above studies. 50 All volunteers were healthy males and received a single dose of 12 mg of copanlisib. Using radioactivity, the primary means of elimination of the drug was in the feces (64%) and urine (22%).…”
Section: Efficacymentioning
confidence: 99%